INFLUENCE OF WORK-FAMILY CONFLICT AND FAMILY-WORK CONFLICT ON EMPLOYEESâ TURNOVER INTENTIONS WITH GENDER, SOCIAL SUPPORT AND INDIVIDUAL VALUE AS MODERATING EFFECTS - Yunita, Putu Irma; Kismono, Gugup (Journal of Indonesian Economy and Business, 2014)
work interfering with family-WIF and family interfering with work-FIW) and its influences onturnover intention. This research also examined the moderating effect of gender, social supportand individual values on the relationship between the work-family conflict and turnoverintentions. The participants of this study were 210 low and middle managers of four and fivestar hotels in Bali. This sample consisted of 126 males and 84 females. Multiple regression andhierarchical methods were used to test the proposed hypotheses. The result showed that WIFpositively and significantly influences the turnover intention but FIW did not. It was also foundthat social support significantly moderates the relationships between variables studied, butgender and individual value had no impact on it.Keywords: turnover intention, work interfering with family, family interfering with work,gender, social support, individual value.